1996
DOI: 10.1074/jbc.271.48.30318
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Major Histocompatibility Complex Class II Molecules in HeLa Cells Promotes the Recruitment of AP-1 Golgi-specific Assembly Proteins on Golgi Membranes

Abstract: The newly synthesized major histocompatibility complex (MHC) class II molecules, an ␣␤ dimer associated with the Ii invariant chain, must be targeted to endosomal, lysosomal enzyme-rich compartments in order to bind and present immunogenic peptides. The precise route followed by this complex at the exit of the transGolgi network, the last sorting station of the biosynthetic pathway, is poorly understood. We show here that overexpression of ␣␤Ii complexes in HeLa cells promotes the first step of clathrin-coat a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
47
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 25 publications
2
47
1
Order By: Relevance
“…After 48 h of maturation, the internal Langerin pool was markedly reduced or absent. At this time point, confocal images taken with fixed acquisition parameters (Salamero et al, 1996) showed a significant decrease in the intensity of total cell anti-Langerin fluorescence ( Figure 9H). Moreover, the anti-Langerin mAb rapidly lost its ability to spontaneously internalize in LCs undergoing maturation (compare Figure 9, E and F, to D).…”
Section: Langerhans Cell Maturation Abolishes Langerin Cycling and Rementioning
confidence: 99%
See 1 more Smart Citation
“…After 48 h of maturation, the internal Langerin pool was markedly reduced or absent. At this time point, confocal images taken with fixed acquisition parameters (Salamero et al, 1996) showed a significant decrease in the intensity of total cell anti-Langerin fluorescence ( Figure 9H). Moreover, the anti-Langerin mAb rapidly lost its ability to spontaneously internalize in LCs undergoing maturation (compare Figure 9, E and F, to D).…”
Section: Langerhans Cell Maturation Abolishes Langerin Cycling and Rementioning
confidence: 99%
“…After fixation and permeabilization the cells were labeled simultaneously with an FITC-conjugated anti-CD1a mAb and phalloidine-TRITC, to study in LCs the effects of cytochalasin D and latrunculin A on the organization of actin filaments, or with CTR-433 followed by donkey anti-mouse TRITC and finally an FITC-conjugated anti-CD1a mAb to visualize in LCs the effects of BFA on Golgi distribution. Confocal laser scanning microscopy and immunofluorescence quantification were performed as previously described (Salamero et al, 1996) by using a Leica TCS4D confocal microscope (Leica Microsystems, Heidelberg, Germany). …”
mentioning
confidence: 99%
“…Newly synthesized MHCII -Ii is directed to the endocytic system with the aid of two classical leucinebased sorting motifs (Bonifacino and Traub 2003) that are embedded within the Ii cytoplasmic domain (Pieters et al 1993;Odorizzi et al 1994;Rodionov and Bakke 1998;Hofmann et al 1999). These motifs can interact with the cytosolic trans-Golgi-network-associated proteinsorting complex AP1 (Salamero et al 1996) and with the plasma membrane adaptor AP2 (Rodionov and Bakke 1998;Hofmann et al 1999). The cytoplasmic extension of the human p35 isoform can be phosphorylated by protein kinase C, a requirement that may be essential for chaperoning MHCII directly from the TGN to endosomes (Spiro and Quaranta 1989;Anderson and Roche 1998;Anderson et al 1999), and in human cells, the AP1-directed pathway may become important particularly during DC maturation (Santambrogio et al 2005).…”
Section: Biosynthesis Of Mhciimentioning
confidence: 99%
“…Leucine-based sorting signals in the cytoplasmic tails bind to 1 or ␤1 adaptin (19,20). AP-1 binding cargo molecules are the mannose-6-phosphate receptors, MPR46 and MPR300, the lysosomal membrane protein, LAMP 1, the invariant chain of the major histocompatibility complex class II receptor, the CD3␥ subunit of the TCR␣␤⅐CD3 receptor complex and the varicella zoster virus glycoprotein I (21)(22)(23)(24)(25)(26)(27).…”
mentioning
confidence: 99%